Polish Lace Makers: Gender, Heritage, and Identity, Anna Sznajder (2020). Issue 2 (1st September 2020) - Quarini, Carol
Polish Lace Makers: Gender, Heritage, and Identity, Anna Sznajder (2020)London: Lexington Books, 320 pp., ISBN 978-1-49858-431-9, £75.00